2023
DOI: 10.3390/medicina60010017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Three versus Four Mini-Implants Retaining Mandibular Overdenture: A 5-Year Randomized Clinical Trial

Asja Celebic,
Ines Kovacic,
Nikola Petricevic
et al.

Abstract: Background and Objectives: Due to a lack of long-term clinical studies that would clarify whether the insertion of three mini-implants (MDIs) can be as successful treatment as the insertion of four MDIs for the retention of mandibular overdentures (ODs), this 5-year prospective cohort study was set up. Materials and Methods: Participants (n = 83) randomly received either four or three MDIs and a mandibular OD. Clinical examinations were performed at the baseline, as well as after one, three, and five years, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Even the insertion of only three MDIs in the mandible for complete OD retention showed very good outcomes in a five-year clinical study [15]. Insertion of two MDIs showed good survival rates and low amounts of marginal bone loss only when used for retention of removable partial dentures [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even the insertion of only three MDIs in the mandible for complete OD retention showed very good outcomes in a five-year clinical study [15]. Insertion of two MDIs showed good survival rates and low amounts of marginal bone loss only when used for retention of removable partial dentures [16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Narrow implants are usually made of Ti90Al6V4 alloy, which has better mechanical properties than pure titanium. The insertion of four MDIs made of Ti90Al6V4 alloy in the mandible has been approved as a successful treatment option for the retention of a mandibular OD in many prospective clinical studies [1][2][3][4][5][6][7][8][9][10][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The four-MDI model represented the reference model, since four single-unit MDIs have been recommended to be placed interforaminally by a manufacturer. Furthermore, the insertion of four MDIs made of Ti90Al6V4 alloy in the intraforaminal region of the mandible, with rubber O-rings in metal housings for OD retention, has been a successful treatment option over a longer period of clinical observation [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The strains in peri-implant bone and the strains from distal edentulous areas under denture saddles are important factors predicting the long-term success of implants which support an OD, especially when knowing that a decrease in implant diameter may increase the stress transferred to the bone–implant interface [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical studies reported survival rates ranging from 95 to 100%, small amounts of peri-implant bone loss, and increased patients’ satisfaction [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A recent study found out that even only three MDIs can be sufficient for satisfactory five-year clinical outcomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%